GLOBAL SALAFISM DAN PENGARUHNYA DI INDONESIA - Ubaidillah Ubaidillah (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
This paper aims to describe the Salafi movement in an effort to spreadits ideology throughout the world (global salafism) and its influence inIndonesia. With socio-historical approach, the history and the ideology of Salafimovement can be revealed and understood, which causes them is known as afundamental religious streams, revivalist, or transnational. The efforts to spreadthe ideology of the Salafi movement all over the world are in the giving ofscholarships to students to study in the Arab Saud Kingdom with theirpetrodollar funds, and alumni become agents of the spread of Salafi ideology intheir various countries. In addition, translation of Arabic books containing theteachings of Salafi ideology is also encouraged, with a variety of languages in theworld. In fact, current Salafi movement started to spread in the economicdomain, such as the sale of honey and habbatussauda, and the treatment ofcupping therapy in various clinics in different countries, as well as in Indonesia.